Social weaving of women for the health of the Commune 1 Popular of Medellín - Cano-Bedoya, Sara María; Martínez-Herrera, Eliana; Posada-Zapata, Isabel Cristina (Iberoamerican Journal of Development Studies, 2022)
The role of women’s care in the territorial transformation represents, in a natural manner in the community, an extension of the domestic space in the community development field. To understand this, a qualitative research was carried out in contexts of inequality based on the experience of eight professional women, thirty-eight and sixty-two years old, mothers and heads of household, with historical and leadership responsibilities in their neighborhoods and microterritories of the Popular Commune 1. Among the discourses recorded, intentions, fears, errors, and difficulties in exercising social participation in health are revealed by the complex institutional and community tensions. Even so, women assume social participation in health as a way of life, and health, particularly as an issue that transcends the health sector and creates opportunities for well-being.